Cultivating Integrity: Exploring the Impact and Implementation of Ethical Leadership across Industries - Astiwardhani, Winny; Santoso, Budi; Sobandi, A. (Journal of Business and Management Review, 2024)
Research Aims: The aim of this research is to explore the impact of ethical leadership across various industries, identify key principles and best practices, and provide strategies for fostering ethical behavior within organizations. Design/methodology/approach: This research employs a Systematic Literature Review (SLR) method to analyze and synthesize ethical leadership studies from 2014 to 2024, ensuring a comprehensive and objective overview. Research Findings: The research findings highlight that ethical leadership, characterized by principles such as honesty, integrity, and effective communication, positively impacts organizational outcomes across various industries. Theoretical Contribution/Originality: The originality of this research lies in its comprehensive synthesis of ethical leadership practices across diverse industries and cultural contexts, offering a nuanced understanding of how ethical principles can be effectively tailored and applied to various organizational settings for improved outcomes. Keywords: Ethical Leadership; Industry-Specific Leadership; Leadership Practices; Integrity in Leadership; Leadership Development